PENGARUH PENGGUNAAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) DALAM PEMBELAJARAN PKn DI SEKOLAH DASAR - Yesya, Dwi Putri; Desyandri, Desyandri (Universitas Negeri Padang, 2014)
The study aims to determine the effect of model CTL to the learning outcomes of students for citizenship education. The method used is a quasi-experimental methods. This study was conducted in SDN 18 Sungai Salak. The sample in this study consisted of two groups, the experimental group numbering and the control group were numbered 38 students. Based on data analysis usin t-test conducted on the significant level α = 0,05, indicates that the learning outcomes of student who are taught model CTL obtained tcount 2,7604 and ttabel 1,68830, with the result that tcount < ttable. It can be concluded that there is significant relationship between learning model CTL on students learning outcomes.Keyword: CTL model, citizenship education, students learning outcomes.